2003
DOI: 10.1007/s00421-002-0785-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training in male prepubertal and pubertal monozygotic twins

Abstract: Nine male pairs of monozygotic twins aged 11-14 years, height 147 (7.6) cm and body mass 39.7 (9.6) kg, participated in this study. Twin zygocity was tested using morphological, dermatoglyphic and hematologic methods, and Tanner's five stages were used for the evaluation of biological maturation. One twin from each pair undertook training for 6 months, three times a week, with running at 85-120% of the lactate anaerobic threshold (LT). Anthropometrics, determination of maximum O(2) uptake (.VO(2max)), LT and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
5
28
0
5
Order By: Relevance
“…First, there were an insufficient number of family studies deriving results from independent samples. Second, although we were able to obtain heritability estimates from three twin studies, these estimates were uninformative since the 95% CI covered the whole range (0,1) (apart from Danis and colleagues who estimated heritability without utilizing DZ twins in its design [27]), and differences between the r MZ and r DZ were not statistically significant (Table 1). Instead, we were able to pool the r MZ for selected outcomes, giving us quantitative estimates of the upper bound of heritability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there were an insufficient number of family studies deriving results from independent samples. Second, although we were able to obtain heritability estimates from three twin studies, these estimates were uninformative since the 95% CI covered the whole range (0,1) (apart from Danis and colleagues who estimated heritability without utilizing DZ twins in its design [27]), and differences between the r MZ and r DZ were not statistically significant (Table 1). Instead, we were able to pool the r MZ for selected outcomes, giving us quantitative estimates of the upper bound of heritability.…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 studies (nine twin studies [20, 2730, 3235] and two family studies [24, 36]) which investigated body composition measures and their response following a PA intervention. Pooling of eight twin studies results (excluding Danis and colleagues [27] due to different methodology) suggest there is a significant r MZ across the majority of body composition measures (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The running speed corresponding to a blood lactate accumulation of 4 mM has been observed to increase following training 72 73. Intervention studies have reported high intensity74 75 but not low intensity58 76 training to result in a decrease in blood lactate accumulation during subsequent submaximal exercise.…”
Section: Aerobic Fitness and Sportmentioning
confidence: 99%
“…15 This finding may be a result of maturation, where VO2 continues to increase through the age of 18, 13 combined with genetic limitations governing oxygen consumption. 5 Training may also influence VO2max, contributing to approximately 35% of the variance of the increase. These measures of aerobic capacity are higher than those reported in junior and amateur rugby league players from Australia 11,12 but lower than those values reported in other national team players.…”
mentioning
confidence: 99%